INTEGRATED MODEL OF BUYING BEHAVIOR OF UKRAINIAN CONSUMERS - KOROVINA, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the factors influencing the behavior of Ukrainian consumers in the conditions that have developed through the prism of the integrated model of consumer behavior and F. Kotler's "black box".  An unstable external environment, martial law, and business digitalization are making adjustments to the purchasing behavior of Ukrainian consumers. The Ukrainian consumer, in today's conditions, has begun to be responsible for the purchase process: he thoughtfully buys the necessary goods, thinks about a strategic reserve in case of unforeseen situations and voluntarily allocates money from his own budget for the needs of the Armed Forces of Ukraine and help for his compatriots who, in particular, lost their families and property during the Russian aggression.The article provides an economic analysis of purchasing trends of modern Ukrainian consumers, consumer behavior in offline and online stores, reasons for changes in the purchasing process, consumer attitudes, etc. Modern trends in purchasing behavior are indicated. An integrated model of consumer behavior is considered. The integrated model with a "black box" acts as a basic multifactor model of purchasing behavior that helps businesses understand the sequence of consumer actions when making a decision to purchase a product. But the changes that are taking place in the external environment and the awareness of consumers require an update of the view on modeling the purchasing behavior of consumers in modern conditions. Taking into account the influence of modern controlled factors, which cause the digitization of business and the possibilities of Internet marketing, an improved integrated model of consumer behavior in the conditions of the situation in Ukraine is proposed.
Keywords: purchasing behavior; consumer; model of consumer behavior; integrated model of consumer behavior